Coitus to expedite the onset of labour: a randomised trial - Omar, N.S.; Tan, P.C.; Sabir, N.; Yusop, E.S.; Omar, S.Z. (Elsevier, 2013)
Objective To evaluate the effect of suggesting coitus as a safe and effective means to expedite labour on pregnancy duration and requirement for labour induction. Design A randomised trial. Setting Antenatal clinic in a university hospital in Malaysia. Population Women from 35 weeks of gestation with an uncomplicated singleton pregnancy. Methods The advise-coitus arm was counselled that coitus at term is a safe, natural and effective means to initiate labour and to avoid labour induction. The control arm was told coitus was safe. Both arms were asked to record coital activity. Main outcome measures Pregnancy duration and labour induction. Results The intervention to delivery interval (mean +/- SD) was 3.2 +/- 1.4 versus 3.3 +/- 1.3 weeks (P = 0.417), with a gestational age at delivery of 39.4 +/- 1.2 versus 39.5 +/- 1.2 weeks (P = 0.112), and with labour induction rates of 126/574 (22.0) versus 120/576 (20.8) (P = 0.666) for the advise-coitus and control arms, respectively, with no statistical difference between the groups. Coitus prior to delivery was more often reported in the advise-coitus arm compared with the control arm: 481/574 (85.3) versus 458/576 (79.9) (RR 1.5, 95 CI 1.12.0, P = 0.019). Also, the median (interquartile range) reported number of coital acts of 3 (25) versus 2 (14) (P = 0.006) was higher for the advise-coitus arm. Other pregnancy and neonatal outcomes did not differ between the groups. Conclusions Labour onset and labour induction did not differ in the advise-coitus arm.